First Report of Powdery Mildew Caused by Podosphaera xanthii on Verbena brasiliensis in Korea - Cho, S E (Plant disease, 2014)
Verbena brasiliensis Vell., commonly known as Brazilian verbena, is native to South America and has been introduced into North America, coastal Europe, southern Africa, and Australasia. Though partly cultivated for garden use, it is invasive in riverine areas and also on roadsides, forest margins, pastures, and waste areas (4). In Korea, this plant was first reported in 1998 in Jeju Island and has become widely naturalized by replacing indigenous plants and disrupting native ecosystems in most of southern part of Korea (3). Since 2009, powdery mildew on Brazilian verbena has been consistently found in several locations of Busan City, Korea. Symptoms appeared as circular to irregular white patches, which subsequently showed abundant hyphal growth on both sides of the leaves and on stems. High disease severity caused poor growth of the plants, resulting in premature senescence and reduced flowering. Specimens (n = 5) were deposited in the Korea University Herbarium (KUS). Appressoria on the mycelium were nipple-shaped or nearly absent. Conidiophores were 140 to 190 × 11 to 12.5 μm and produced 2 to 7 immature conidia in chains with a crenate outline. Foot-cells in conidiophores were straight, cylindric, relatively short, 50 to 65 μm long, and constricted at the very base of branching point from the hypha. Conidia were hyaline, ellipsoid to ovate, measured 28 to 38 × 18.5 to 22 μm (length/width ratio of 1.2 to 1.8), and contained distinct fibrosin bodies. Germ tubes were produced from the lateral position of conidia. No chasmothecia were observed. These structures are typical of the powdery mildew Euoidium anamorph of the genus Podosphaera. The morphological characteristics and measurements were consistent with those of P. xanthii (Castagne) U. Braun & Shishkoff (1). To confirm the identity, the complete internal transcribed spacer (ITS) region of rDNA of the isolate KUS-F27220 was amplified with primers ITS1/ITS4, and sequenced. The resulting 477-bp sequence was deposited in GenBank (Accession No. KJ472787). A GenBank BLAST search of this sequence revealed 100% identity with Podosphaera sp. on V. bonariensis and V.× hybrida from Japan (AB462804 and AB040347). The Podosphaera sp. isolates listed above are now placed in P. xanthii (1). Pathogenicity was confirmed through inoculation by gently pressing a diseased leaf onto leaves of three healthy, potted 2-month-old Brazilian verbena plants. Three non-inoculated plants served as controls. Inoculated plants developed signs and symptoms after 6 days, whereas the control plants remained symptomless. The fungus present on the inoculated leaves was identical morphologically to that originally observed on diseased plants. Powdery mildew of Verbena spp. associated with Podosphaera sp. (including Sphaerotheca sp.) has been globally reported, but not on V. brasiliensis (1,2). To our knowledge, this is the first report of powdery mildew disease caused by P. xanthii on V. brasiliensis globally. Our field observations suggest that the powdery mildew could limit expansion of V. brasiliensis in Korea. References: (1) U. Braun and R. T. A. Cook. Taxonomic Manual of the Erysiphales (Powdery Mildews), CBS Biodiversity Series No.11. CBS, Utrecht, 2012. (2) D. F. Farr and A. Y. Rossman. Fungal Databases. Syst. Mycol. Microbiol. Lab., Online publication, ARS, USDA, Retrieved February 18, 2014. (3) C. G. Song and Y. H. Yang. The Naturalized Plants in Jeju Island. Nam-Jeju County, Jeju, Korea, 2005. (4) P. F. Yao. Kew Bull. 45:101, 1990